Association of Gut Microbiota With Intestinal Ischemia/Reperfusion Injury - Chen, Jingyi; Wang, Yu; Shi, Yongxia; Liu, Yongpan; Wu, Chengyi; Luo, Yanrong (Frontiers in Cellular and Infection Microbiology, 2022)
Intestinal ischemia/reperfusion (II/R) is a common acute and critical condition in clinical practice with a high mortality rate. However, there is still a lack of effective prevention and treatment measures for II/R injury. The role of the gut microbiota in II/R has attracted widespread attention. Recent evidence has demonstrated that the gut microbiota plays a pivotal role in the occurrence, development, and prognosis of II/R. Therefore, maintaining the homeostasis of gut microbiota and its metabolites may be a potential strategy for the treatment of II/R. This review focuses on the importance of crosstalk between the gastrointestinal ecosystem and II/R to highlight II/R-induced gut microbiota signatures and potential applications of microbial-based therapies in II/R. This will also provide potentially effective biomarkers for the prediction, diagnosis and treatment of II/R.